2016
DOI: 10.1016/j.meegid.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Population diversity of Theileria annulata in Portugal

Abstract: The tick-borne protozoan parasite Theileria annulata causes tropical theileriosis, a severe disease of cattle that occurs across the Mediterranean littoral, the Middle East and Southern Asia. In the Mediterranean region, the disease has long been perceived as being a constraint to livestock production in North Africa and Turkey but was believed to have minimal impact in Southern European countries. It has recently been demonstrated that in Southern Portugal the prevalence of T. annulata is approximately 30%. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
5
20
3
Order By: Relevance
“…Genomic sequence analysis has allowed the identification of putatively neutral, polymorphic micro-and mini-satellite markers for economically important Theileria spp. which has facilitated population genetic analysis of T. parva (Oura et al, 2003) and T. annulata (Weir et al, 2007;Al-Hamidhi et al, 2015;Gomes et al, 2016) in a number of endemic regions. More recently, a set of genetic markers has been established for T. lestoquardi and, at present, only one Omani study has applied these markers to examining diversity in field populations of the parasite (Al-Hamidhi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequence analysis has allowed the identification of putatively neutral, polymorphic micro-and mini-satellite markers for economically important Theileria spp. which has facilitated population genetic analysis of T. parva (Oura et al, 2003) and T. annulata (Weir et al, 2007;Al-Hamidhi et al, 2015;Gomes et al, 2016) in a number of endemic regions. More recently, a set of genetic markers has been established for T. lestoquardi and, at present, only one Omani study has applied these markers to examining diversity in field populations of the parasite (Al-Hamidhi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the global genetic sub-structure of T. annulata have shown a high level of genetic differentiation between Turkey and Tunisia (Weir et al, 2007). Studies have also shown a low level of genetic differentiation in T. annulata within-countries including Turkey, Tunisia, Oman, China and Portugal (Al-Hamidhi et al, 2015; Gomes et al, 2016; Weir et al, 2011; Yin et al, 2018), reflecting high levels of animal movement, or translocation of ticks.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a diverse range of parasite genotypes was identified in the vaccinated cattle over a disease season (Fig 2) and non-vaccinated animals at Day 105 of the sampling period (Fig 3B). Geographical sub-structuring at a large geographical scale has been documented between T. annulata populations in Tunisia, Turkey, Portugal and Oman (Al-Hamidhi et al, 2015;Gomes et al, 2016;Weir et al, 2007), but this has not been clearly demonstrated at the within-country level. In this study, a diverse range of parasite genotypes was observed in vaccinated animals on six different farms located within the same district (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…Male and female gametes are formed which fuse to form zygotes, which in turn differentiate into kinetes that migrate to the salivary glands, ultimately generating bovine-infective sporozoites (Gauer, 1995;Schein and Friedhoff, 1978). Recent population genetic studies have provided further indirect evidence for the occurrence of a sexual phase in the parasite life cycle and these indicate that random mating is a feature of field populations of T. annulata (Al-Hamidhi et al, 2015;Gomes et al, 2016;Weir et al, 2007). Sexual recombination, together with a high transmission rate, is understood to play a significant role in generating T. annulata genetic diversity in different regions (Katzer et al, 2006;Pumpaibool et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation